Unusual Polymicrobial Wound Infections In Healthy Patient After Cesarean Sectio - Tan, Henny Tannady; Elena, Irene Maria; Dharmawan, Ade; Layanto, Nicolas (Jurnal Midpro, 2020)
Cesarean delivery often complicated by surgical site infection, wound infection and endometritis. No study mention Multidrug Resistant Klebsiella pneumonia and Acinetobacter lwofii were isolated.Here we report a rare case of polymicrobial wound infections in healthy patient after Cesarean Sectio caused by Pseudomonas aeruginosa, Multidrug Resistant Klebsiella pneumonia and Acinetobacter iwofii. A 30-year-old woman at 37 weeks gestation (G1P0A0) presented to our hospital for cesarean sectio due to oligohydroamnios and malpresentation. She came to us on the eleventh post-delivery day with discharge from her surgical wound. Intraoperative cultures revealed Pseudomonas aeruginosa, Multidrug Resistant Klebsiella pneumonia and Acinetobacter lwofii.The greatest contribution to risk for surgical site infection was associated with maternal obesity and hypertensive disorder, but she has no risk factor.The polymicrobial combination of our patient’s is unique from previously described studies, in this case all were Gram negative bacteria (Pseudomonas aeruginosa, Multidrug Resistant Klebsiella pneumonia and Acinetobacter lwofii).